James Madison papers - Madison, James, 1751-1836.
Correspondence, memoranda, autobiography, notes of debates in the Continental Congress (1776) and the Federal Convention (1787), and related material, largely 1771-1836. Correspondents include Jaquelin Ambler, James Barbour, Joel Barlow, William Harris Crawford, Henry Dearborn, Albert Gallatin, Elbridge Gerry, Alexander Hamilton, Thomas Jefferson, Rufus King, Henry Lee, James Monroe, Edmund Pendleton, Edmund Randolph, Caesar A. Rodney, Benjamin Rush, Richard Rush, Nicholas Philip Trist, George Washington, and Alexander White.
Available through the Library of Congress Web site.
Microfilm edition available, in part
In part, transcripts and photocopies.
U.S. president and secretary of state, delegate to the U.S. Continental Congress, and U.S. representative from Virginia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ambler, Jaquelin, -- 1742-1798 -- Correspondence; Barbour, James, -- 1775-1842 -- Correspondence; Barlow, Joel, -- 1754-1812 -- Correspondence; Crawford, William Harris, -- 1772-1834 -- Correspondence; Dearborn, Henry, -- 1751-1829 -- Correspondence; Gallatin, Albert, -- 1761-1849 -- Correspondence; Gerry, Elbridge, -- 1744-1814 -- Correspondence; Hamilton, Alexander, -- 1757-1804 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; King, Rufus, -- 1755-1827 -- Correspondence; Lee, Henry, -- 1756-1818 -- Correspondence; Madison, Dolley, -- 1768-1849 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Pendleton, Edmund, -- 1721-1803 -- Correspondence; Randolph, Edmund, -- 1753-1813 -- Correspondence; Rodney, C. A. -- 1772-1824 -- Correspondence; Rush, Benjamin, -- 1746-1813 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Trist, Nicholas Philip, -- 1800-1874 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; White, Alexander, -- 1738-1804 -- Correspondence; United States. -- Continental Congress; United States. -- Constitutional Convention -- (1787); United States -- History -- Confederation, 1783-1789.; United States -- History -- Constitutional period, 1789-1809.; United States -- History -- War of 1812.; United States -- Politics and government -- 1809-1817.; Cabinet officers; Delegates, U.S. Continental Congress -- Virginia; Presidents -- United States; Representatives, U.S. Congress -- Virginia